BEHAVIOURAL MANAGEMENT OF CHILDREN WITH VARIOUS INTELLECTUAL DISABILITIES – A PRACTICAL GUIDE - Vasilica Toma; Tiberiu Băsăscu; Cristina Cenușă; Carmen Savin; Ana Sîrghe; Veronica Șerban-Pintiliciuc; Alina Adumitroaie; Foia Cezar; Mihalaș Eugeniu; Marciuc Daniel; Loredana Golovcencu (Romanian Journal of Oral Rehabilitation, 2023)
Oral health professionals and caregivers alike agree that children with disabilities, whether acquired or developmental, have the right to receive proper rehabilitation, in order to obtain their maximal functioning potential and lead a normal life. Aim of the study This paper aims to review the main challenges faced by paediatric dentists in the management of children with various intellectual disabilities, and formulate a set of recommendations and guidelines designed to enhance disabled patients’ trust in dental therapists, while enabling the latter to successfully carry out specific oral health procedures on this group of vulnerable individuals. Material and methods A review of available literature was performed, searching MedLine and PubMed databases for terms like: children, intellectual disability, prevention, dental treatment. Results Difficulties that arise in the context of dental management of a disability may be overpassed with a few techniques and methods available for the general dentist and the paediatric dentist alike. Conclusions Educating the paediatric dentist regarding the most common oral manifestations of intellectual disabilities is important, and guidelines are necessary in order to properly manage the dental treatment of this population group.